Taxonomy of an Liot Device Based upon Production Functions - Hammerström, Lennart; Zwerenz, Dirk; Giebe, Carsten (European Journal of Economics and Business Studies, 2019)
In this essay, we develop a decision model for the economic impact of Industry 4.0 technologies/IIoT devices on established business processes by testing two hypotheses concerning a decision model based on production functions. New methods to aid in the design and modelling of production systems that are able to rapidly reconfigure and that are self-adaptive in response to disruption (both by humans and for automated systems) are required (Sanderson, Chaplin, - Ratchev, 2019).Mass customization, shorter product lifecycles, smaller production batches and higher production variability lead to the requirement for manufacturing systems to be rapidly reconfigurable and self-adaptive in response to disruption, We propose to recover and apply available and established techniques to evaluate and assess the rationale of technologies before they are implemented to improve the decision process. We consider the investment into IIoT devices from a microeconomic perspective as a long-run problem for companies and therefore consider those problems to be reviewed with adequate methodologies to build a consistent decision model. Investing into a factor (such as an IIoT device) is only economically reasonable as long as this factor produces a benefit, otherwise the investment infringes upon economic feasibility (Fandel 2005).
Keywords: taxonomy, liot, device, production, functions